A novel wearable assistive device for jaw motion disability rehabilitation : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Auckland, New Zealand - Wang, Xiaoyun (Massey University, 2014)
Temporomandibular disorder (TMD) is a group of dysfunctions in the masticatory system that cause muscle stiffness and weakened masticatory ability. TMD is commonly suffered by a considerate percentage of the population, impairs oral hygiene and brings inconveniences to a great number of patients. The therapeutic exercise with significant efficacy is widely advised among patients in the treatment of the mandibular hypomobility to reduce pain and increase the inter-incisal opening of the mouth. This thesis proposes a novel wearable device to passively assist to deliver the mandibular movement. The mandible, attached to the skull via masticatory muscles and pivoted at the condyles at the temporomandibular joint (TMJ), can be simplified as moving in the two-dimensional sagittal plane. A planar four-bar linkage was synthesized to reproduce the specified normal jaw motion in terms of incisor and condyle trajectory on the coupler point to meet the kinematic specification. Adjustable lengths of the links were used to achieve a group of trajectories of any possibility. The prototype of the linkage has been fabricated, integrated with the sensory units and electronic hardware into a Mechatronic system. The dynamics of the entire system was analyzed, along with the model thoroughly built up in Simulink, to facilitate further controller design. A closed-loop control scheme based on the device was proposed, and it is able to achieve the accurate position control to the crank to ensure the position of the jaw to be notified. A series of experiments with the device has been carried to evaluate the performance of the controller, with the control algorithm implemented into a micro-controller based board. The exoskeleton was then evaluated in terms of the kinematic and dynamic interaction in the hybrid human-machine system, in which the condyle movement was recorded by AG500 tracking machine. Simulation and experimental methods were respectively developed to investigate the joint force which is in-vivo inaccessible. Simulation was conducted by adding the dynamic model of the mandible into the linkage model with controller. A test-rig was designed to mount the skull and the jaw replicas which simulated the counterparts in human body. Experiments were carried to evaluate the joint force and the performance of the controller; results obtained from both simulations and experiments have indicated the force level inside the TMJ is rather small compared with the one in the circumstance where maximum chewing force is applied.
Keywords: Robotic jaw; Robotic exoskeleton design; Mastication simulation; Temporomandibular disorder (TMD); Jaw motion disability; Assistive device design